The green industrial revolution energy, engineering and economics - Clark, Woodrow; Cooke, Grant (Butterworth-Heinemann, 2015)
The new green industrial revolution is driven by a variety of global environmental concerns. In some regions, it is spurred by the scarcity of cheap affordable renewable energy that will also lead to a reduced reliance on fossil fuel in the production of power. In others, it is driven by a need to reduce greenhouse gas (GHG) emissions from power generation. This book provides a comprehensive review of the most popular green “disruptive technologies in energy production as well as their economic impact. In addition, the book includes a multitude of international case studies where these technologies are currently deployed and their economic impact on the region.--Provided by publisher.